The Implementation of Education Character through the Qur'an Memorization Program at SMP IT Bina Insani Metro Utara - Adi Wijaya (CV. Creative Tugu Pena, 2025)
This study aims to analyze the implementation of character education through the tahfidz Al-Qur’an program at SMP IT Bina Insani Metro Utara and to identify the supporting and inhibiting factors that influence its execution. Character education is understood as a systematic effort to cultivate students who are not only intellectually capable but also possess noble character and strong moral values. The tahfidz program serves as a strategic medium for instilling religious values, honesty, discipline, hard work, creativity, environmental awareness, and responsibility. Through teacher exemplification, school regulations, and the habituation of worship and daily positive activities carried out consistently, students demonstrate significant improvement in spiritual development, daily behavior, and learning attitudes. The findings indicate that the success of the tahfidz program is supported by several factors, including strong family involvement, students’ internal motivation, and teachers’ competence in guiding memorization. However, the study also identifies inhibiting factors such as limited parental engagement in monitoring memorization progress, varied teacher understanding of character value implementation, and shortages in qualified tahfidz instructors. This study concludes that synergy among schools, teachers, and families is essential to optimize the effectiveness of character education through tahfidz Al-Qur’an. Strengthening collaboration and enhancing teacher competencies will enable the tahfidz program to function more comprehensively as an instrument for shaping students' character.